2021
DOI: 10.1016/j.isci.2021.102227
|View full text |Cite
|
Sign up to set email alerts
|

LIFR-α-dependent adipocyte signaling in obesity limits adipose expansion contributing to fatty liver disease

Abstract: The role of chronic adipose inflammation in diet-induced obesity (DIO) and its sequelae including fatty liver disease remains unclear. Leukemia inhibitory factor (LIF) induces JAK-dependent adipocyte lipolysis and altered adipo/cytokine expression, suppressing in vivo adipose expansion in normal and obese mouse models. To characterize LIF receptor (LIFR-a)-dependent cytokine signaling in DIO, we created an adipocyte-specific LIFR knockout mouse model (Adipoq-Cre;-LIFR fl/fl). Differentiated adipocytes derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Cachexia is observed in 50% of all solid tumor patients, responsible for 30% of all cancer-related deaths, and ultimately an independent risk factor for reduced cancer-specific mortality ( 1 , 4 ). Obesity, a disease of adipose excess, represents the opposite end of the metabolic spectrum from cachexia with net increases in adipose triglyceride content while still associated with similar cytokine profiles and signaling events in adipose tissue ( 5 7 ). Obesity is a significant risk factor in the development of metabolic syndrome and cancer development, affecting morbidity and mortality in 1/3 of the world’s population.…”
Section: Introductionmentioning
confidence: 99%
“…Cachexia is observed in 50% of all solid tumor patients, responsible for 30% of all cancer-related deaths, and ultimately an independent risk factor for reduced cancer-specific mortality ( 1 , 4 ). Obesity, a disease of adipose excess, represents the opposite end of the metabolic spectrum from cachexia with net increases in adipose triglyceride content while still associated with similar cytokine profiles and signaling events in adipose tissue ( 5 7 ). Obesity is a significant risk factor in the development of metabolic syndrome and cancer development, affecting morbidity and mortality in 1/3 of the world’s population.…”
Section: Introductionmentioning
confidence: 99%
“…In mice and humans, increased IFI16 levels are associated with larger adipocytes, enhanced inflammatory state, and impaired insulin-stimulated glucose uptake in white adipose tissue [ 78 ]. STAT3 is a relevant transcription factor of proinflammatory genes in adipocytes that is associated with adipocyte inflammation [ 79 , 80 ]. RELA is a relevant transcription factor associated with adipocyte inflammation [ 81 ] that inhibits adipogenesis and accumulation of lipids in adipocytes [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…In support of this, we find that Empagliflozin increases nuchal white adipose tissue by decreasing nuchal brown fat depots ( Figure 9 ). Indeed, other studies have shown that increasing the capacity within this adipose depot correlates with diminished liver steatosis, independent of glucose and insulin tolerance [ 59 ]. Taken together, our data suggest that alteration of renal glucose handling promotes healthy adipose expansion thereby reducing lipid accumulation within tissues such as the visceral fat and liver, in the male TallyHo mice.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our data suggest that alteration of renal glucose handling promotes healthy adipose expansion thereby reducing lipid accumulation within tissues such as the visceral fat and liver, in the male TallyHo mice. This expansion has been linked to several signaling pathways including STAT3 and growth hormone receptor [ 55 , 59 , 60 ]. Clearly, future work is needed to determine if Empagliflozin, either directly or indirectly, influences these pathways that regulate expansion and white adipose lipogenesis.…”
Section: Discussionmentioning
confidence: 99%